2018
DOI: 10.31793/1680-1466.2018.23-4.362
|View full text |Cite
|
Sign up to set email alerts
|

Justification of the need for correction selenium status in the treatment of thyrotopathy among Ukrainians (review of literature and their own observations)

Abstract: The review analyzes the evidence base presented in scientific publications, which proves the importance of selenium for normal functioning of the thyroid gland. Presented data have connections with the involvement of selenium in the formation of thyroid hormones, their distribution in organs and systems, and peripheral metabolism. The role of the main selenoproteins participating in these processes is specified. The data of PubMed on the availability of selenium to residents of European countries is given, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Therefore, irrespective of the presence or absence of AO, most patients with GD exhibited severe Se deficiency, which requires administration of selenium agents. These findings are in agreement with those reported by other studies on selenium deficiency in thyroid disorders in Ukraine, with severe selenium deficiency observed in patients with autoimmune thyroid disorders [17].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, irrespective of the presence or absence of AO, most patients with GD exhibited severe Se deficiency, which requires administration of selenium agents. These findings are in agreement with those reported by other studies on selenium deficiency in thyroid disorders in Ukraine, with severe selenium deficiency observed in patients with autoimmune thyroid disorders [17].…”
Section: Resultssupporting
confidence: 93%
“…In addition, Se deficiency can exacerbate the effects of iodine deficiency and the same is true for vitamin A or iron deficiency [15,16]. Se deficiency has shown to be a key environmental factor which is thought to precipitate autoimmune thyroid disease in several parts of the world deficient in soil Se [17]. The regulation and metabolism of thyroid hormones require a steady supply of Se, and environmental Se levels strongly correlate with serum Se levels [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Even in such countries as Great Britain, the intake of selenium with food products has decreased by 50% [26]. By now, monitoring studies have been conducted in European countries, including Ukraine, which revealed a defi ciency of selenium in the population's diet [22,27,28].…”
mentioning
confidence: 99%
“…(повтор). At the same time, the defi ciency of selenium in the diet of the population has a global scale [15][16][17][18][19][20][26][27][28].…”
mentioning
confidence: 99%